Some Further Remarks on Preference Proximity - Baigent, Nick (Quarterly Journal of Economics, 1989)
Journal Article Some Further Remarks on Preference Proximity Get access Nick Baigent Nick Baigent Tulane University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 104, Issue 1, February 1989, Pages 191–193, https://doi.org/10.2307/2937841 Published: 01 February 1989